Solitude and fear during the great coronavirus war - Chiara Catania (The Beryl Institute, 2020)
When you get ill, the first thing that comes to your mind is, “Will I make it? Will I survive?". COVID19 has a major impact on mental health. A sadness that inundates us like a river in flood and which we cannot hold back. But the thing that torments is the solitude. Those who struggle towards recovery do it alone, and those who do not make it die alone. An emblematic experience of a sense of loneliness, depression and death during illness is deeply described. We tell how the love of family and friends can help to recover from the abyss. Fighting this battle and winning it alone is painful. A lonely death is even more painful. We must stick together virtually and think about each other. The work done with enormous strength and tenacity by doctors and nurses is a great hope for a better time. It does raise the hope that a future generation will be able to truly take care of mankind. When all this ends, we must not go back to normal. We must be reborn, better. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.